Evaluation of Quality of Life in Patients with Chronic Leg Wounds: Can Platelet-rich Plasma Therapy Help? - Rainys, Domantas; Čepas, Adas; Rimdeika, Rytis (Lietuvos chirurgija, 2020)
Aim. The aim of the study was to evaluate and compare the quality of life (QoL) using platelet-rich plasma gel (PRP) and conventional treatment of chronic leg wounds. Methods. Randomized clinical trial was carried out in Hospital of Lithuanian University of Health Sciences Kaunas Clinics during 2014–2018. Patients (n = 69) included in the study were randomly grouped into 2 groups: 1) PRP, 2) Control. SF-36 questionnaire was used to evaluate QoL, visual analog scale was used to evaluate persistent pain associated with ulcer and wound exudate volume was also evaluated. Statistical analysis were performed with SPSS 23.0 package. Results. Patients in PRP group at the end of the treatment rated their QoL over control group patients (p
Keywords: chronic wound; skin ulcer; platelet-rich plasma; quality of life; regenerative medicine